jzs.10358 - Al-Majidi, S M. H.; Alfraij, Redhab A.J (Sulaimani Journal for Pure and Applied Sciences, 2015)
New 1,2,4-triazine, imidazole ,2-aminothiazole, phthalazine and oxazoline derivatives of 2-mercapto-3-phenyl-4(3H)-quinazolinone were synthesized via an important intermediate compound(2) In which formed from reaction of compound(1) with chloroacetyl chloeide in dimethylformamide. The following different steps show the details of this work: The first step involves the conversion of compound (2) in to thiosemicarbazide and thiourea derivatives through its reaction with thiosemicarbazide,thiourea respectively to give compounds 3 and 4. Then cyclization of compounds 3 and 4 by using alkaline media 4N NaOH and concentrated H2SO4 to give compounds (5, 6 and 7) respectively. The second step involves treating compound (2) with hydrazine hydrate in dimethylformamide to give compound (8). Then reaction of prepared compound (8) with different aromatic anhydrides in acetic acid as a solvent to gives compounds (9-13). The third step involves preparation of compounds (14, 15 and 16) via reaction of compound (8) with (1-naphthyl isocyanate, phenylisocyanate and phenyl thioisocyanate) respectively in absolute ethanol. Then cyclization of compounds 14, 15 and 16 with alkaline media in the presence of 4N NaOH and p-bromophenacyl bromide to give compounds (17-22) respectively. The fourth step involves reaction of the prepared compound (8) with carbon disulfide in the presence of potassium hydroxide producing compound (23). The obtained salt (23) was treated with hydrazine hydrate to afford the desirable compound (24). The structure of newly synthesized compounds were identified by spectral methods such as FTIR, 1H-NMR, 13C-NMR, some other physical Properties and some specific reactions.
Keywords: quinazolinone 1,2,4triazine imidazole 2amino thiazole Phthalazine oxazoline antimicrobial